Transformation of spinel crystals structure МgО·nАІ₂O₃ under high-temperature annealing - Belykh, G.I.; Gritsyna, V.T.; Lytvynov, L.A.; Kolner, V.B. (Functional Materials, 2009)
The processes at high temperature annealing of non-stoichiometric МgО·nАІ₂O₃ spinel crystals (n = 2.2) in O₂ atmosphere at 1300-1500°C have been investigated. A gradual non-stoichiometry increase up to n = 2.8 has been found with increasing annealing time due to MgO evaporation followed by formation of polycrystalline α-АІ₂O₃ phase. The structure and composition МgО·nАІ₂O₃ layer grown at the sapphire surface in MgO vapor of at 1500-1800°C have been studied. The formation of amorphous phase in transition zone from hexagonal sapphire structure with a piling sequence ABABAB into spinel cubic one with sequence of atomic layers ABCABC was established.